Social accounting and Quesnay's model - Fernández López, Manuel (1988)
Early attempts of quantitative economic analysis may be found in the works of Petty, Davenant, King, Cantillon, Quesnay, Turgot, and others, from the end of 17th century up to mid-18th century. In their works they employed various kinds of approach, e.g. numerical analysis, statistics, income analysis, etc. to such a degree of elaboration that some of their results can be translated to modern economic techniques.